Pore Filling of Spiro-OMeTAD in Solid-State Dye-Sensitized Solar Cells Determined Via Optical Reflectometry - Docampo, P; Hey, A; Guldin, S; Gunning, R; Steiner, U; Snaith, H (2012)
A simple strategy is presented to determine the pore-filling fraction of the hole-conductor 2,2-7,7-tetrakis-N,N-di-pmethoxyphenylamine-9,9- spirobifluorene (spiro-OMeTAD) into mesoporous photoanodes in solid-state dye-sensitized solar cells (ss-DSCs). Based on refractive index determination by the film's reflectance spectra and using effective medium approximations the volume fractions of the constituent materials can be extracted, hence the pore-filling fraction quantified. This non-destructive method can be used with complete films and does not require detailed model assumptions. Pore-filling fractions of up to 80% are estimated for optimized solid-state DSC photoanodes, which is higher than that previously estimated by indirect methods. Additionally, transport and recombination lifetimes as a function of the pore-filling fraction are determined using photovoltage and photocurrent decay measurements. While extended electron lifetimes are observed with increasing pore-filling fractions, no trend is found in the transport kinetics. The data suggest that a pore-filling fraction of greater than 60% is necessary to achieve optimized performance in ss-DSCs. This degree of pore-filling is even achieved in 5 μm thick mesoporous photoanodes. It is concluded that pore-filling is not a limiting factor in the fabrication of "thick" ss-DSCs with spiro-OMeTAD as the hole-conductor. © 2012 WILEY-VCH Verlag GmbH and Co. KGaA, Weinheim.